Transformative Multimodal Activities Enhance Sustainable and Impactful English Listening Comprehension - Diah Retno Anggraini; N Nargis; El Kahfi Rafi Fazli Mubarak; Olyvia Reggina Maria Margareth (Prosiding University Research Colloquium, 2026)
This study investigates how transformative multimodal activities boost English listening comprehension in a meaningful and lasting way. By combining visual aids, physical movement, and concept mapping, students actively engage with listening materials. Results show significant improvement in comprehension, retention, and motivation. The study highlights that multimodal approaches make English listening learning more effective, enjoyable, and impactful.